(untitled) (Journal of Business and Economics, 2026)
Consumer behaviour involves how individuals, groups, or companies select, purchase, use, and dispose of products and services. This systematic review examines the influence of culture and learning on consumer behaviour in developing countries, particularly Ethiopia and Africa. Drawing on business, psychology, marketing, and sociology, it analyses trends in peer-reviewed articles published between 2016 and 2026 to provide insights for marketers, educators, and future research on emerging markets. The study employed a literature review method based on the PRISMA 2020 framework to ensure transparency and accuracy. Researchers searched databases including Web of Science, Emerald, Google Scholar, and Scopus for relevant peer-reviewed articles from 2016 to 2026. After rigorous screening and selection based on predefined criteria, 35 studies were included in the analysis. Cultural factors such as norms, family influence, community values, and traditional beliefs significantly shape consumer attitudes and purchasing decisions. Consumer learning processes, including product experience, advertising exposure, and word-of-mouth, also influence knowledge formation and purchase intentions. The findings highlight key implications for marketers and educators in developing countries like Ethiopia and other emerging markets, while identifying gaps for further consumer behaviour research.